2021
DOI: 10.1016/j.adaj.2020.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations of COVID-2019–related multisystem inflammatory syndrome in children: a review of 47 pediatric patients

Abstract: Background. Although much is still unknown about the full effects of COVID-19, literature from the early stages of the COVID-19 pandemic (spring and summer 2020) supports a postviral immunologic reaction resulting in a multisystem inflammatory syndrome in children (MIS-C). The purpose of this study was to report the rates of documented oral and oropharyngeal manifestations among these patients and to determine the association of these findings with other MIS-C symptoms.Methods. The authors conducted a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 43 publications
0
40
0
7
Order By: Relevance
“…Multiorgan involvement is common in these patients, and cardiogenic or vasoplegic shock can occur in 32–76% of patients [ 1 , 7 , 11 , 27 , 28 , 32 ]. Patients may also present with mucous membrane involvement (27–76%), lymphadenopathy (6–16%), and swollen hands or feet (9–16%) [ 1 , 4 , 7 , 10 , 11 , 20 , [29] , [30] , [31] , [32] , [38] , [39] , [40] ]. Pleural effusions, pericardial effusions, and ascites can also occur in these patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiorgan involvement is common in these patients, and cardiogenic or vasoplegic shock can occur in 32–76% of patients [ 1 , 7 , 11 , 27 , 28 , 32 ]. Patients may also present with mucous membrane involvement (27–76%), lymphadenopathy (6–16%), and swollen hands or feet (9–16%) [ 1 , 4 , 7 , 10 , 11 , 20 , [29] , [30] , [31] , [32] , [38] , [39] , [40] ]. Pleural effusions, pericardial effusions, and ascites can also occur in these patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mainstay of treatment for MIS-C is immunomodulation in those with shock, cardiac involvement, or severe disease manifestations requiring intensive care unit admission [ 1 , 4 , [6] , [7] , [8] , 10 , 40 , 42 , 59 , 60 ]. While there are no prospective studies to date, expert recommendations using data extrapolated from KD advise intravenous immunoglobulin (IVIG) as first-line therapy in doses of 2 g/kg administered every 8–12 h [ 1 , 4 , [6] , [7] , [8] , 10 , 40 , 42 , [59] , [60] , [61] ]. Recent retrospective data have also suggested a potential benefit of early initiation of corticosteroids (prednisolone 2 mg/kg/day given intravenous or oral in 3 divided doses for 10 days), particularly in critically ill children and those on multiple vasoactive medications [ 1 , 4 , 7 , 20 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported oral lesion was oral ulceration which was reported in up to 47% (n = 27) of the cases in one study. 12 Other common oral mucosal changes included changes in the tongue including strawberry tongue, geographic tongue, fissured tongue and macroglossia which has even led to a terminology ‘covid tongue’, 13 , 14 , 15 , 16 with one study reporting these changes in up to 25% of the cases (n = 10). 16 Gingival manifestations included necrotic gingivitis and desquamative gingivitis.…”
Section: Resultsmentioning
confidence: 99%
“…To that end, Bordea and colleagues report a systematic review of guidelines to provide safe and efficacious oral care during the COVID-19 pandemic [ 31 ]. A retrospective study of 47 multisystem inflammatory syndromes in children (MIS-C) positive pediatric patients, who tested positive for COVID-19 infection, concluded that dental care providers play an important role in the early detection of MIS-C and in the identification of oral lesions in MIS-C patients [ 32 ]. They posit, furthermore, that MIS-C incidence is likely to increase as the number of COVID-19 positive cases continues to grow.…”
Section: Discussionmentioning
confidence: 99%